AKTOR POLITIK KONTEMPORER DALAM PERSPEKTIF PSYCHOCULTURAL - Asri, Syamsul (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2013)
Today, the post industrial era of digital modernity presents politics as a popular, non-elitism, day to day discourse. Even everyone may be a politician, who are aware of their surrounding power relation and get constantly involved in formulating political vision and mission, regardless of internal irrational overlapping interests. The contemporary political actors, whether or not they like it, have to disclose themselves to all possible approaches applied by any groups of people including both local businessmen and multinational capitalists, whose latter multilayered interests dominate structural politics. Politics of image culminates the actors’ existence, while the media plays amplifying roles and this point runs as a symbiosis; using the Panopticon concept of Foucault, a contemporary political actor as well as a subject and an object of Panopticon. Whether or not he was aware, Foucault had been trapped within a network of communication which either he himself established it or outsider’s systemic power did it. This in turn bears undisputable injustices sentiment among the very original owners of the polis; the demos or the people.